Implementasi Kurikulum Merdeka Belajar dalam Meningkatkan Motivasi Belajar Siswa Kelas X di SMA Muhammadiyah 1 Sukoharjo - Muhammad Fajrul Shodiq; Edy Muslimin; Muhammad Yunan Hidayat (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study explores the implementation of the Independent Learning Curriculum (Kurikulum Merdeka Belajar) and its impact on enhancing learning motivation among Grade X students at SMA Muhammadiyah 1 Sukoharjo during the 2023/2024 academic year. Employing a descriptive qualitative method, the research involved field observations, interviews with school leaders, teachers, and students, and document analysis. The findings reveal that the curriculum was implemented through three structured phases: planning, implementation, and evaluation. In the planning phase, the school prioritized teacher training, teaching module preparation, and infrastructural readiness. The implementation phase was marked by differentiated instruction, project-based learning, and diagnostic assessments tailored to student needs. The evaluation phase emphasized reflection and continuous improvement. As a result, students demonstrated increased motivation, characterized by higher engagement, improved classroom atmosphere, and enhanced self-confidence. The study found a decline in the number of students categorized as